A study of factors influencing the sensitivity to antibody of tanned, ovalbumin-coated, formalinized sheep red cells - Herbert, W. J. (1967)
Comparative tests were done to find the best conditions under which formalinized sheep red cells can be tanned and then coated with chromatographically purified ovalbumin. Variation in the time taken for tanning or coating, the amount of antigen used, the temperature during coating, the use of different batches of tannic acid, ovalbumin or of cells formalinized by different methods had little effect on sensitivity to agglutination by antibody. A slight increase in sensitivity was obtained by coating at a low pH, by increasing the quantity of tannic acid employed and by heat denaturation of the antigen.